The duality of religious identity and self-understanding in the novel (The Cloud Player) by Ali Badr is an example - Noor Khalil Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Player of the Clouds), the writer presents a narrative tone based on the theme of religious violation, when the narrator masters writing the text creatively by fragmenting the understanding of another, who worked to break the heroic self that represented suffering, of the one who disappointed him / the other, who represented the axis of conflict, which is revealed by the character. And the circumstances that helped form it as a violationThe reality of the hero, to live a state of psychological rupture by rejecting the reality that seemed to pursue him in all directions (political, social, and religious), and in all places (inside and outside the country), thus framing for a dual personality before the mind of the reader, one party representing Western culture, and one party representing religious authorities, thus creating Our creative text is based on the conflict between two violated realitiesIt contains identity, fragments of self-understanding, and with the skill of the narrator, the reader experiences representations of the conflict and suffering of the heroic characterIt breaks the reader’s horizon of expectations, creating for a creative text based on the conflict between two realities in which identity is violated, self-understanding is fragmented, and with the skill of the narrator, the reader experiences representations of the conflict and suffering of the heroic character